Testing how teachers' self-efficacy and student-teacher relationships moderate the association between bullying, victimization, and student self-esteem. Issue 6 (2nd November 2021) - van Aalst, Danelien A.E.; Huitsing, Gijs; Mainhard, Tim; Cillessen, Antonius H.N.; Veenstra, René
ABSTRACT: This study investigated how teachers' self-efficacy for intervening in social dynamics and teacher-student relationships directly impact students' self-esteem, and indirectly buffer the negative association between both bullying and victimization and students' self-esteem. Teachers play a key role in shaping the peer relations in the classroom, and they might also be able to lessen the negative impact of bullying and victimization on students' self-esteem. Multilevel regression analysis on a sample of 59 Dutch teachers and 1, 490 of their 5th grade students indicated that student-reported bullying and victimization were negatively related to students' self-reported self-esteem. Better student-perceived student-teacher relationships were related to higher self-esteem for all students, with additional increases in self-esteem for victims but decreases in the self-esteem of bullies. Teacher-reported self-efficacy was only related to lower self-esteem in bullies. Implications of these results and suggestions for further research are discussed.